Draft genome sequence of Karnal bunt pathogen (Tilletia indica) of wheat provides insights into the pathogenic mechanisms of quarantined fungus. - Anil Kumar; Vishakha Pandey; Manoj Singh; Dinesh Pandey; M S Saharan; Soma S Marla (PLoS ONE)
Karnal bunt disease in wheat is caused by hemibiotrophic fungus, Tilletia indica that has been placed as quarantine pest in more than 70 countries. Despite its economic importance, little knowledge about the molecular components of fungal pathogenesis is known. In this study, first time the genome sequence of T. indica has been deciphered for unraveling the effectors' functions of molecular pathogenesis of Karnal bunt disease. The T. indica genome was sequenced employing hybrid approach of PacBio Single Molecule Real Time (SMRT) and Illumina HiSEQ 2000 sequencing platforms. The genome was assembled into 10,957 contigs (N50 contig length 3 kb) with total size of 26.7 Mb and GC content of 53.99%. The number of predicted putative genes were 11,535, which were annotated with Gene Ontology databases. Functional annotation of Karnal bunt pathogen genome and classification of identified effectors into protein families revealed interesting functions related to pathogenesis. Search for effectors' genes using pathogen host interaction database identified 135 genes. The T. indica genome sequence and putative genes involved in molecular pathogenesis would further help in devising novel and effective disease management strategies including development of resistant wheat genotypes, novel biomarkers for pathogen detection and new targets for fungicide development.